Amplified multipartite entanglement witnessed in a quantum critical metal - Yuan Fang; Mounica Mahankali; Yiming Wang; Lei Chen; Haoyu Hu; Silke Paschen; Qimiao Si (Nature Communications)
Abstract Strong correlations in matter promote a landscape of quantum phases and associated quantum critical points. For metallic systems, there is increasing recognition that the quantum criticality goes beyond the Landau framework and, thus, further means are needed to characterize the quantum critical fluid. Here we do so by studying an entanglement quantity, the quantum Fisher information, in a strange metal system, focusing on the exemplary case of an Anderson/Kondo lattice model near its Kondo destruction quantum critical point. The spin quantum Fisher information peaks at the quantum critical point and indicates a strongly entangled ground state. Our results are supported by the quantum Fisher information extracted from inelastic neutron scattering measurements in heavy fermion metals. Our work elucidates the loss of quasiparticles in strange metals, opens a quantum information avenue to advance the understanding of metallic quantum criticality in a broad range of strongly correlated systems, and points to a regime of quantum matter to realize amplified entanglement.